Evaluasi Kinerja Ruas Jalan Raya Singosari, Kecamatan Singosari Kabupaten Malang - Malo , Suryadi Harming; Arifianto , Andy Kristafi ; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
The land transportation system has two important aspects, namely transportation facilities and infrastructure. If the need for transportation facilities (road transport) is not matched by the availability of transportation infrastructure (road), transportation problems will arise. Transportation problems that can be caused by this imbalance are traffic jams. Singosari is a district in Malang Regency, East Java Province, Indonesia. This sub-district is located north of Malang City, this sub-district is crossed by the Surabaya-Malang main route and is included as the worst traffic jam area in Malang.Malang City is a city located in East Java Province, Indonesia, the second largest city in East Java after Surabaya, and the 12th largest city in Indonesia. The city was founded during the Kingdom of Kanjempuan and is located on a plateau of 145.28 km2 which is located in the middle of Malang Regency. Together with Batu City and Malang Regency, Malang City is part of a unitary region known as Malang Raya. (Source: Surya Malang.Com)With this rapid development also has an impact on traffic activities in the city of Malang. The impact that occurs on traffic activities is congestion on the road, this is because many activities on the highway are used to get to one place to another. One of the frequent traffic jams is on the Singosari road in Singosari District, Malang. From the results of the above analysis, it is known that the characteristics of the Singosari road segment are referred to as a low side obstacle class and have a high enough vehicle volume that is 3404 km / hr.